Deep learning approach implementation in natural and social science learning at an outstanding Primary School: A case study - Neni Vila Prawardhani; Winarno; Fadhil Purnama Adi (Journal of Professional Teacher Education, 2026)
The implementation of deep learning in Indonesia's curriculum remains underexplored in non-urban outstanding primary schools. This study aimed to analyse the characteristics of natural and social sciences deep learning practice and the ecosystem factors supporting its implementation in an outstanding primary school. Three upper-grade teachers (Grades IV, V, VI) served as primary participants, with 10 to 29 years of teaching experience. Data were collected through in-depth interviews, a focus group discussion (FGD), classroom observations conducted three times per teacher using a four-dimension rubric adapted from the framework for teaching, and analysis of instructional planning documents. Analysis employed Braun and Clarke's thematic analysis with source and method triangulation. Findings revealed three consistently occurring pedagogical strategies: contextual phenomenon-based trigger questions, distributed collaborative role structures within learning groups, and metacognitive reflection rituals at the close of instruction. The mean observation score was 3.50 on a 4-point scale, indicating transformative practice, while document completeness reached 16 of the 16 required document types. These three strategies were supported by two ecosystem factors: transformational principal leadership and an active internal learning community. The theoretical implication is a redefinition of teacher readiness as a collective capacity emerging from multilevel interactions, rather than a static individual attribute. The practical implication is the need for professional development interventions targeting the school ecosystem holistically.